1994
DOI: 10.1016/0091-3057(94)90235-6
|View full text |Cite
|
Sign up to set email alerts
|

PRE-084, a σ selective PCP derivative, attenuates MK-801-induced impairment of learning in mice

Abstract: -084, a aselectivePCPderivative, attenuates MK-8Ol-induced impairment of learning in mice. PHARMACOL BIOCHEM BEHAV 49(4) [859][860][861][862][863][864][865][866][867][868][869] 1994.-We investigated the effect of the tr selective PCP derivative PRE-084 on the impairment of learning induced in mice by the noncompetitive NMDA antagonist MK-801. Learning capacities were evaluated using the spontaneous alternation in a Y-maze test for spatial working memory, the step-down passive avoidance and the elevated plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0
5

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 33 publications
4
74
0
5
Order By: Relevance
“…Ligands selective for σ1 receptors have been reported to exert antidepressant-like, anxiolytic and analgesic actions in preclinical studies (Hayashi et al, 2011). In addition, σ1 receptor occupation has been linked to neurorestorative effects and has been suggested as a novel therapeutic target for the treatment of cognition deficit (Maurice et al, 1994;Urani et al, 1998;Maurice, 2002;Espallergues et al, 2007;Antonini et al, 2011;van Waarde et al, 2011;Kourrich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands selective for σ1 receptors have been reported to exert antidepressant-like, anxiolytic and analgesic actions in preclinical studies (Hayashi et al, 2011). In addition, σ1 receptor occupation has been linked to neurorestorative effects and has been suggested as a novel therapeutic target for the treatment of cognition deficit (Maurice et al, 1994;Urani et al, 1998;Maurice, 2002;Espallergues et al, 2007;Antonini et al, 2011;van Waarde et al, 2011;Kourrich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ligands selective for σ1 receptors have been reported to exert antidepressant-like, anxiolytic and analgesic actions in preclinical studies (Hayashi et al, 2011). In addition, σ1 receptor occupation has been linked to neurorestorative effects and has been suggested as a novel therapeutic target for the treatment of cognition deficit (Maurice et al, 1994;Urani et al, 1998;Maurice, 2002;Espallergues et al, 2007;Antonini et al, 2011;van Waarde et al, 2011;Kourrich et al, 2012).Our laboratory previously reported on the neuroprotective properties of the σ1 receptor ligand, LS-1-137, which is a novel N-(benzylpiperidin)phenylacetamide that binds to the σ1 receptor with high affinity (Ki value = 3.2 nM) and exhibits 80-fold binding selectivity for the σ1, over the σ2 receptor . LS-1-137 was found to protect HT-22 neuronal cells from glutamate-induced cell death and LS-1-137 was found in vivo to significantly reduce the ischaemic lesion volume in rats using a transient middle cerebral artery occlusion model of stroke (Luedtke et al, 2012).…”
mentioning
confidence: 99%
“…Endogenous sigma-ligands are not known, although progesterone has been suggested to be one of them (7)(8)(9). Possible sigma-site-mediated drug effects include modulation of glutamate receptor function, neurotransmitter response, neuroprotection, behavior, and cognition (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Most of these studies implied that sigma-binding sites are plasmalemmal elements of the signal transduction cascade.…”
mentioning
confidence: 99%
“…Pharmacological studies have showed that NMDA receptor antagonists impair the cognitive functions [21][22][23] and that NMDA receptor agonists enhance memory tasks [24]. Previous studies have demonstrated that systemic injection of CPP dose-dependently inhibited spatial short-term memory in the Y maze test [17].…”
Section: Resultsmentioning
confidence: 99%